Asal-Usul Manusia Menurut Teori Evolusi: Tinjauan Antropologis-Teologis dan Implikasinya - Wesly, Jhon (STTI Harvest Semarang, 2024)
In contrast to evolutionary theory that sees humans as the result of natural selection from lower species, an Anthroplogical-Theological perspective grounded in the teachings of the Bible asserts that humans are God's noblest creation, created consciously with a specific purpose for the glory of God. This research discusses the various forms of evolutionary theory and objections to it from an Anthroplogical-Theological perspective, as well as underlining the importance of restoring God's image through redemption. This scientific work was written using the literature study research method. Data was obtained through searching various sources such as scientific articles, books and other literature related to the research topic. The results show that Theological Anthropology views humans as created in the image and likeness of God who inherits the image and nature of God, responsible for maintaining relationships with God, others and preserving His creation. The damaged image of God can be restored through the redemptive work of Christ. The theory of evolution should be criticized from an Anthropological-Theological perspective regarding its implications in contemporary Christianity in the fields of philosophy, ethics, morals, socio-culture, Christian education and ecological studies. Suggestions for further research related to Christian biology, Christian anthropology, Christian ethics, Christian education and eco-theology. AbstrakBerbeda dengan Teori Evolusi yang melihat manusia sebagai hasil seleksi alam dari spesies yang lebih rendah, perspektif Antroplogi-Teologis yang berpijak pada ajaran Alkitab menegaskan bahwa manusia adalah ciptaan Allah yang termulia, diciptakan secara sadar dengan tujuan spesifik untuk kemuliaan Allah. Penelitian ini membahas berbagai bentuk Teori Evolusi dan keberatan terhadap teori tersebut dari sudut pandang Antropologi-Teologis, serta menggarisbawahi pentingnya pemulihan gambar Allah melalui penebusan. Karya ilmiah ini ditulis menggunakan metode penelitian studi pustaka. Data diperoleh melalui penelusuran berbagai sumber seperti artikel ilmiah, buku-buku serta literatur lain yang berkaitan dengan topik penelitian. Hasil penelitian menunjukkan bahwa Antropologi-Teologis memandang manusia diciptakan sesuai gambar dan rupa Allah yang mewarisi citra dan sifat Allah, bertanggung jawab memelihara relasi dengan Tuhan, sesama dan melestarikan alam ciptaan-Nya. Gambar Allah yang rusak dapat dipulihkan melalui karya penebusan Kristus. Teori Evolusi patut dikritisi dari sudut pandang Antropologi-Teologis terkait implikasinya dalam kekristenan masa kini baik di bidang filsafat, etika, moral, sosial-budaya, pendidikan Kristen dan studi ekologis. Saran untuk penelitian lanjutan terkait biologi Kristen, antropologi Kristen, etika Kristen, pendidikan Kristen dan eko-teologi.